Clinical utility of targeted next‐generation sequencing for the diagnosis of myeloid neoplasms with germline predisposition. Issue 9 (16th July 2021) - Andrés‐Zayas, Cristina; Suárez‐González, Julia; Rodríguez‐Macías, Gabriela; Dorado, Nieves; Osorio, Santiago; Font, Patricia; Carbonell, Diego; Chicano, María; Muñiz, Paula; Bastos, Mariana; Kwon, Mi; Díez‐Martín, José Luis; et al.
Abstract : Myeloid neoplasms (MN) with germline predisposition (MNGP) are likely to be more common than currently appreciated. Many of the genes involved in MNGP are also recurrently mutated in sporadic MN. Therefore, routine analysis of gene panels by next‐generation sequencing provides an effective approach to detect germline variants with clinical significance in patients with hematological malignancies. Gene panel sequencing was performed in 88 consecutive and five nonconsecutive patients with MN diagnosis. Disease‐causing germline mutations in CEBPα, ASXL1, TP53, MPL, GATA2, DDX41, and ETV6 genes were identified in nine patients. Six out of the nine patients with germline variants had a strong family history. These patients presented great heterogeneity in the age of diagnosis and phenotypic characteristics. In our study, there were families in which all the affected members presented the same subtype of disease, whereas members of other families presented various disease phenotypes. This intrafamiliar heterogeneity suggests that the acquisition of particular somatic variants may drive the evolution of the disease. This approach enabled high‐throughput detection of MNGP in patients with MN diagnosis, which is of great relevance for both the patients themselves and the asymptomatic mutation carriers within the family. It is crucial to make a proper diagnosis of these patients to provide them with the most suitable treatment, follow‐up, and genetic counseling. Abstract : Germline predisposition to hematologic malignancies was historically thought to be rare; however, a widespread use of novel technologies has led to an enlarged description of familial cases and the number of mutations involved. This review discusses how the identification of an inherited predisposition syndrome allows to optimize the management of the patient and the opportunities for identification other family members at risk.